2011
DOI: 10.3325/cmj.2011.52.446
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental factors on marijuana use in 11 European countries

Abstract: AimTo investigate the association between environmental factors (perceived availability of marijuana, perceived use among friends and siblings, use of alcohol and tobacco, family structure, parental control, school performance) and lifetime prevalence and frequent and early marijuana use in high school students.MethodsWe used self-reported data from 15-16 years old participants of the 2003 European School Survey Project on Alcohol and Other Drugs (ESPAD) conducted in 11 countries: Denmark, Estonia, Norway, Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The subscales that mostly characterized the subsamples of drug users were ES and Dis. These results confirm previous data in adolescence literature where Dis, ES, and SSS total score are the measures most associated with all drug categories' use [ 2 ].…”
Section: Discussionsupporting
confidence: 91%
“…The subscales that mostly characterized the subsamples of drug users were ES and Dis. These results confirm previous data in adolescence literature where Dis, ES, and SSS total score are the measures most associated with all drug categories' use [ 2 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although most teens do not escalate from trying drugs to developing addictive behaviors, even experimenting with substances is a problem. Namely, substance misuse can develop into a pattern of risky behavior including intoxicated driving, unsafe sex, injecting, and violent behavior [ 2 , 3 , 4 ] Therefore, even when adolescents do not develop symptoms of dependence (i.e., repeated substance misuse), even the rare usage of substances can pose a serious health-related risks and lead to socially dangerous behavior, with problems including family problems, failure in school (i.e., educational failure), altered interest in everyday healthy activities (i.e., proper eating, physical exercise), chemsex, mental health problems, impaired memory (i.e., problems with learning), risky sexual behavior with consequent increased risk of contracting infectious diseases (i.e., hepatitis C, HIV), etc. [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, cultural and environmental factors such as cannabis availability might help to explain the difference between our findings and those of previous studies. Although several studies have shown that the availability seems to be a relevant influencing factor of initiation and progression to symptoms of cannabis abuse ( 47 , 48 ), literature about the relationship between availability, law on cannabis possession, and cannabis use is yet far from conclusive ( 49 , 50 ). It is beyond the scope of this article reviewing laws on cannabis use, but it is important to note that the Italian law system does not differentiate cannabis-related offenses (such as possession for personal use) from those of any other illegal drugs.…”
Section: Discussionmentioning
confidence: 99%